PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 235 PALEMBANG - Zahara Zahara; Evy Ratna Kartika Waty; Nopri (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to improve student learning outcomes and activities in data presentation material by applying a project based learning model. This research was conducted at SD Negeri 235 Palembang with research subjects in class IV B, totaling 26 students. The research method uses the type of classroom action research which consists of the stages of planning, implementing action, observing, and reflecting. The research data is in the form of observation results and student test assessment results. Before the action was given, only 34.61% of students were able to achieve a KKM of 68. After the action was taken using the project based learning model, cycle I showed that there was an increase in student learning outcomes with learning outcomes of 46.1%, cycle II of 69.2%, and cycle III of 80.1%. In addition to learning outcomes, the activities of students also increased, seen during the implementation of observations and learning process activities carried out in class each cycle became more active. The result of active learning of students in cycle I was 58.01%, cycle II was 68.58% and cycle III was 81.72%. So it can be concluded that by applying the project based learning model can improve learning outcomes and students' activeness in learning mathematics data presentation material.